An Engaging, Yet Failed Flip - Kevin S. Krahenbuhl (Park University, 2017)
The flipped classroom is growing significantly as a model of learning in higher education. However, there are ample problems with the research on flipped classrooms, including where success is often defined by student perceptions and a lack of consistent, empirical research supporting improved academic learning. This quasi-experimental study describes a semesterlong comparison of two of the same courses taught by the same instructor utilizing a primarily didactic lecture approach and a flipped classroom approach. The experiment found results in which students in the didactic lecture class had significantly higher end-of-course scores than those in the flipped classroom; however, with regards to a document-based analytic essay question there was no statistically significant difference.